If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -2) + -3(x + -1) = 0 Reorder the terms: 4(-2 + x) + -3(x + -1) = 0 (-2 * 4 + x * 4) + -3(x + -1) = 0 (-8 + 4x) + -3(x + -1) = 0 Reorder the terms: -8 + 4x + -3(-1 + x) = 0 -8 + 4x + (-1 * -3 + x * -3) = 0 -8 + 4x + (3 + -3x) = 0 Reorder the terms: -8 + 3 + 4x + -3x = 0 Combine like terms: -8 + 3 = -5 -5 + 4x + -3x = 0 Combine like terms: 4x + -3x = 1x -5 + 1x = 0 Solving -5 + 1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + 1x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + 1x = 0 + 5 1x = 0 + 5 Combine like terms: 0 + 5 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| X^2-14X+49=7 | | (5x+2)+(x^2)=180 | | (.15x)=10.35*3-x | | 12-(x-3)=9 | | 39=1/2(F-32) | | (.15x+x)=10.35*3 | | 16c^2+20c+25=0 | | (.15x+x)/3=10.35 | | X^2-10X+25=4 | | -6x-2=9x^2+12x+1 | | 5x-3=60 | | 17+11(2)=17-7 | | 0=-.018x^2+.25x+.7 | | -56+11(2)=-56-7 | | 5x+3=18+2x | | -15+11(2)=-15-7 | | 20=4-2x | | 9m^2+2=0 | | -29+11(2)=-29-7 | | -3+18+x=21 | | N+11(2)=n-7 | | 19=14k-17 | | 3x+3=2x+7 | | -11-5=4x | | 2(-56)+11=-56-7 | | 2(-29)+11=-29-7 | | 2(17)+11=17-7 | | x+-5=-1 | | 2(-15)+11=-15-7 | | 14-x=5 | | 7-(6-2x)=4y | | 8y-7=9 |